2021
DOI: 10.1186/s12889-021-11969-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between depressive symptoms, anxiety symptoms, their comorbidity and health-related quality of life: a large-scale cross-sectional study

Abstract: Background There were few studies exploring the associations between depressive symptoms, anxiety symptoms and health-related quality of life (HRQoL) in the general population, especially in resource limited area. The aims of this study were to assess the associations between depressive symptoms, anxiety symptoms, their comorbidity and HRQoL in rural area. Methods A total of 23,496 eligible participants from Henan rural cohort were included. The Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
2
5
0
1
Order By: Relevance
“…In the current study, QoL was significantly related to depression and anxiety disorders in both rural and urban residents. Similar findings were reported by Liao et al (2021), who studied almost 24,000 rural residents in China, where both depressive symptoms and anxiety disorders significantly decreased QoL and affected both men and women [52]. Kang et al (2021) presented results confirming that comorbid chronic diseases and unhealthy lifestyle negatively influence QoL.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study, QoL was significantly related to depression and anxiety disorders in both rural and urban residents. Similar findings were reported by Liao et al (2021), who studied almost 24,000 rural residents in China, where both depressive symptoms and anxiety disorders significantly decreased QoL and affected both men and women [52]. Kang et al (2021) presented results confirming that comorbid chronic diseases and unhealthy lifestyle negatively influence QoL.…”
Section: Discussionsupporting
confidence: 85%
“…Women living in urban areas rated their QoL significantly lower than men (p <0.005), but in the case of rural residents, the differences in the assessment of QoL between men and women were not so significant. Nevertheless, Liao et al (2021) found that women in rural populations had lower QoL. They also described a relationship between depressive symptoms and reduced QoL.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also found that anxiety played a role in the decreased EQ‐5D‐5L index values in MSA and lower EQ VAS scores of MSA‐P (Du et al., 2018). Depression and anxiety were associated with a lower EQ‐5D‐5L index value and EQ VAS score in the Chinese elderly (Liao et al., 2021). A previous study found that more severe depressive symptoms were determinants of lower EQ VAS scores in MSA and progressive supranuclear palsy (Winter et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of variance (ANOVA) and Student t test were performed to test the differences in continuous variables. Based on the Chinese value set for the EQ-5D-5L, different domains and different levels had different coefficients (MO = 0.345, SC = 0.253, UA = 0.233, PD = 0.302, AD = 0.258, L 1 = 0, L 2 = 0.191, L 3 = 0.458, L 4 = 0.832, and L 5 = 1), and the utility value calculation formula was as follows: utility = 1 − MO × Ln − SC × Ln − UA × Ln − PD × Ln − AD × Ln ( n = 1, 2, 3, 4, 5) [ 23 ]. The ceiling effect was calculated as the proportion of patients who reported no problems in all dimensions [ 24 ].…”
Section: Methodsmentioning
confidence: 99%